2017
DOI: 10.1161/jaha.117.006802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monthly, High‐Dose, Long‐Term Vitamin D Supplementation on Central Blood Pressure Parameters: A Randomized Controlled Trial Substudy

Abstract: BackgroundThe effects of monthly, high‐dose, long‐term (≥1‐year) vitamin D supplementation on central blood pressure (BP) parameters are unknown.Methods and ResultsA total of 517 adults (58% male, aged 50–84 years) were recruited into a double‐blinded, placebo‐controlled trial substudy and randomized to receive, for 1.1 years (median; range: 0.9–1.5 years), either (1) vitamin D3 200 000 IU (initial dose) followed 1 month later by monthly 100 000‐IU doses (n=256) or (2) placebo monthly (n=261). At baseline (n=5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 51 publications
7
57
0
3
Order By: Relevance
“…Similarly, a recently published substudy using monthly high‐dose vitamin D3 showed an improvement in aortic BP and arterial stiffness measures in those with baseline 25(OH)D levels <50 nmol/L; effect sizes were consistent with our IPD analysis findings for this subgroup. No significant improvements were observed in the overall trial group, however …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Similarly, a recently published substudy using monthly high‐dose vitamin D3 showed an improvement in aortic BP and arterial stiffness measures in those with baseline 25(OH)D levels <50 nmol/L; effect sizes were consistent with our IPD analysis findings for this subgroup. No significant improvements were observed in the overall trial group, however …”
Section: Discussionmentioning
confidence: 79%
“…No significant improvements were observed in the overall trial group, however. 51 Pooled observational data show that a log e difference in PWV (%2.7 m/s) corresponds to a 35% to 45% increase in the risk of a cardiovascular event. A 0.3-m/s improvement in PWV is therefore unlikely to be associated with a clinically important reduction in cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…The Vitamin D Assessment study (ViDA) in 5100 healthy subjects, aged > 50 years, recently reported that 100,000 IU oral vitamin D 3 monthly was neutral for the prevention of CV disease [49,50], with a low rate of 25[OH]D deficiency in participants (25%), a lower than expected endpoint rate and monthly doses cited as possible reasons [51]. Metaanalysis and data from ViDA and other studies describe that benefits on clinical outcomes are greatest in the most deficient, and in studies using daily dosing regimens (as in VINDICATE) rather than monthly [52][53][54][55].…”
Section: Vitamin D As An Interventionmentioning
confidence: 99%
“…Data about the effects of vitamin D supplementation on PWV and central BP have been limited . Two studies in this issue of JAHA address this need, by examining the potential benefits of vitamin D supplementation on arterial stiffness and central BP . In BEST‐D (Biochemical Efficacy and Safety Trial of Vitamin D), 305 community‐dwelling older adults living in the United Kingdom were randomized to receive vitamin D 4000 IU, vitamin D 2000 IU, or placebo for 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Two studies in this issue of JAHA address this need, by examining the potential benefits of vitamin D supplementation on arterial stiffness and central BP. 12,13 In BEST-D (Biochemical Efficacy and Safety Trial of Vitamin D), 305 community-dwelling older adults living in the United Kingdom were randomized to receive vitamin D 4000 IU, vitamin D 2000 IU, or placebo for 12 months. The primary end point in BEST-D was plasma 25-hydroxyvitamin D, and the main findings have been published previously.…”
mentioning
confidence: 99%